A microwave-based system combines drying, extraction and sterilization under low-temperature vacuum conditions - Wei Cheng Chen; Chyun Chau Fuh; Chien Yu Lu; Hsun Heng Tsai (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
This study develops a simultaneous system combining low-temperature drying, extraction, and sterilization under low temperature, by comprising a microwave source and a vacuum chamber. The study commences by investigating the reduction in moisture content under microwave heating in vacuum conditions as a function of the drying time, the material load, and the microwave output power. Subsequently, the study compares the results obtained for the yield and composition of the essential oil extracted from Coleus amboinicus Loureiro leaves using the proposed system with those obtained using a conventional steam distillation technique. Finally, the study investigates the performance of the developed system in inactivating Bacillus subtilis spores using a low-pressure plasma sterilization technique. The experimental results show that the low-temperature vacuum conditions established in the proposed drying system accelerate the rate of moisture removal. Furthermore, the microwaves penetrate the interior of the material, heating the internal moisture directly. This not only reduces the drying time but also preserves the original flavor and appearance of the dried material. The extraction results show no significant difference between the final yield percentages and compositions of the essential oils extracted using the proposed system and the distilled steam technique, respectively. However, the extraction time is reduced from 90 minutes in the distilled steam method to just 30 minutes in the proposed system. Finally, the plasma sterilization results demonstrate that the proposed system reduces the number of colony-forming units of Bacillus subtilis from 170 to 7 within a treatment time of 1 s, and achieves complete sterilization following 180 s.